Autopsy findings of fatal retroperitoneal hemorrhage after traumatic rupture of bilateral renal angiomyolipoma - Enrico De Dominicis; Gian Luca Marella; Gabriele Giuga; Giulia Ceccobelli; Luca Savino; Alessandro Mauro Tavone (University of São Paulo, 2024)
The present work reports the autopsy findings of a unique case characterized by fatal retroperitoneal hemorrhage following the traumatic rupture of bilateral renal angiomyolipomas. Renal angiomyolipomas are generally benign tumors with an unpredictable clinical course, ranging from asymptomatic to sudden rupture and hemorrhagic shock. They may be associated with genetic disorders such as tuberous sclerosis complex. The case under investigation is unprecedented in the medical literature due to its bilateral nature and fatal outcome. Autopsy analysis revealed an extensive retroperitoneal hemorrhage originating from bilateral ruptured tumors. Microscopic examination found features consistent with bilateral renal angiomyolipoma. Circumstantial information identified a traffic accident before the death, considering it as the cause of the tumors' traumatic rupture. In this case, due to the severity of the situation, immediate medical measures-such as fluid resuscitation, coagulopathy correction, and surgical treatment, which are usually lifesaving-could not be performed. This led to the patient being declared dead at the scene of the crash.